GINGERINO: a high sensitivity ring laser gyroscope for fundamental and quantum physics investigation - Giovinetti, Francesco; Altucci, Carlo; Bajardi, Francesco; Basti, Andrea; Beverini, Nicolò; Capozziello, Salvatore; Carelli, Giorgio; Castellano, Simone; Ciampini, Donatella; Di Somma, Giuseppe; Di Virgilio, Angela D. V.; Fuso, Francesco; et al. (Frontiers in Quantum Science and Technology, 2024)
Ring Laser Gyroscopes (RLG), based on the Sagnac effect, are currently the most sensitive rotation sensors. GINGERINO, a RLG installed underground, shows a proved sensitivity that enters the few frad/s regime in about 2.5 days of integration time. On one hand, this sensitivity is well below the shot-noise-level as predicted applying to GINGERINO the so called independent beam model. On the other hand, it paves the way to the use of RLG in fundamental and quantum physics research. Indeed, high sensitivity rotation measurement opens to test general relativity and alternative theory of gravity. Moreover, it make possible to study the interplay between quantum effects in the optical domain and non inertial reference frames.